Ultrafast switching time and third order nonlinear coefficients of microwave treated single walled carbon nanotube suspensions - Kamaraju, N.; Kumar, Sunil; Karthikeyan, B.; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K.; Sood, A. K. (Journal of Nanoscience and Nanotechnology, 2009)
Microwave treated water soluble and amide functionalized single walled carbon nanotubes have been investigated using femtosecond degenerate pump-probe and nonlinear transmission experiments. The time resolved differential transmission using 75 femtosecond pulse with the central wavelength of 790 nm shows a bi-exponential ultrafast photo-bleaching with time constants of 160 fs (130 fs) and 920 fs (300 fs) for water soluble (amide functionalized) nanotubes. Open and closed aperture z-scans show saturation absorption and positive (negative) nonlinear refraction for water soluble (amide functionalized) nanotubes. Two photon absorption coefficient, beta(0) similar to 250 cm/GW (650 cm/GW) and nonlinear index, gamma similar to 15 cm(2)/pW (-30 cm(2)/pW) are obtained from the theoretical fit in the saturation limit to the data for two types of nanotubes.
Keywords: Nonlinear Optical Coefficients; SWCNT; Ultra-Fast Switching